2008
DOI: 10.1080/14622200802443718
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biomarkers of exposure to selected cigarette smoke constituents in adult smokers switched to carbon-filtered cigarettes in short-term and long-term clinical studies

Abstract: Cigarette smoke is a complex aerosol that includes a gas vapor phase and a particulate phase. Inclusion of activated carbon in the cigarette filter can reduce some of the gas-phase smoke constituents implicated as toxicologically relevant. The present study evaluated exposure to selected gas-phase constituents when adult smokers switched to prototype cigarettes with a highly activated carbon filter. Smokers (N = 160) in two separate studies were randomized to continue to smoke conventional cigarettes (either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 23 publications
1
57
1
1
Order By: Relevance
“…Group 3 (n = 20) stopped smoking for the remainder of the study (SS2). Details of this study design, subject characteristics and cigarette characteristics have been reported [18].…”
Section: Studymentioning
confidence: 99%
“…Group 3 (n = 20) stopped smoking for the remainder of the study (SS2). Details of this study design, subject characteristics and cigarette characteristics have been reported [18].…”
Section: Studymentioning
confidence: 99%
“…Biomarkers of tobacco exposure or potential harm have previously been analyzed for cigarette smokers (16)(17)(18)(19)(20)(21)(22), but less information is available about biomarkers associated with cigar consumption. It has been shown that cigar smoke contains significantly higher concentrations of toxic and carcinogenic constituents such as tobaccospecific N-nitrosamines (TSNA), carbon monoxide, and benzene than does cigarette smoke (6).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-one known BoEs for tobacco smoke toxicants with validated analytical methods [13,[23][24][25][26][27][28] were assessed in total (Supplemental Data, Table 1). Levels were reported as quantities of BoEs excreted over 24 h, and were calculated as products of the concentrations in urine and the volumes of urine produced by the subjects over the collection period.…”
Section: Clinical Studymentioning
confidence: 99%
“…For example, BoE levels indicating exposure to nitrosamines were lower in smokers of cigarettes with low tobacco-specific nitrosamine yields than in those who smoke cigarettes with higher yields [12], and reductions were seen in BoEs to some vapourphase toxicants following a switch from cellulose acetatefiltered cigarettes to carbon-filtered cigarettes [13].…”
Section: Introductionmentioning
confidence: 99%